2000
DOI: 10.1006/cbir.1999.0514
|View full text |Cite
|
Sign up to set email alerts
|

Packing of Myosin Molecules in Muscle Thick Filaments

Abstract: The backbone of the myosin filament is an aggregate of alpha-helical coiled coil myosin rods. Its surface forms a three-stranded helix composed of myosin heads. Currently there is no adequate model to describe the organization of the myosin filament. It is proposed here that, in cross-section the light meromyosin (LMM) of 18 myosin molecules form an outer tube, with nine S2 forming the interior core. At the surface of the thick filament, myosin heads are arranged in three rows, giving the filament a periodicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Despite their lower density, however, mutations in the tail region are still capable of causing severe cardiomyopathy. Despite the absence of functional sites, the tail is a highly conserved region of the MYH7 gene with regular bands of charge that have features of an α-helical coiled-coil [41]. Consequently, amino acid substitutions in the tail region may disrupt the assembly or structure of the thick filament component of the sarcomeres [7,38,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their lower density, however, mutations in the tail region are still capable of causing severe cardiomyopathy. Despite the absence of functional sites, the tail is a highly conserved region of the MYH7 gene with regular bands of charge that have features of an α-helical coiled-coil [41]. Consequently, amino acid substitutions in the tail region may disrupt the assembly or structure of the thick filament component of the sarcomeres [7,38,60].…”
Section: Discussionmentioning
confidence: 99%
“…MYH7 was the first sarcomeric protein to be linked with cardiomyopathy [23]. Due to the different properties between the globular head domain (S1), the neck or hinge region (S2) and the tail (light meromyosin) domain of the MYH7 gene [41], mutations may have diverse effects depending on their location. In addition, as a mutation can lead to a change in the amino acid sequence, the structure and interactive properties of the mutant protein may also be altered.…”
Section: Introductionmentioning
confidence: 99%
“…We interpret the experimental data as demonstrating the marked inhibition in dynamic parameters of SM fibers contraction due to noncholinergic effects of chlorpyriphos. Muscle's inability to maintain stable contraction strength under tetanic contraction indicates not only the variability in effects of different chlorpyriphos concentrations upon contractile activity, but also differences in molecular mechanisms of generation of response strength and in propagation of dynamic muscle movements [6,[22][23][24][25]. The observed decrease in dynamic parameters of contraction results probably from direct influen ce of chlorpyriphos on myofilaments unmediated by acetylcholine esterase.…”
Section: +mentioning
confidence: 99%
“…Early modeling work (Squire, 1971(Squire, ,1972(Squire, ,1973 of myosin molecules alone suggested that the two packing arrangements most consistent with experimental data were 1) a hollow-cored "curved crystalline" arrangement in which the individual myosin molecules were not arranged in subfilaments and 2) a solid thick filament composed of subfilaments each composed (at any cross section) of three myosin molecules (see below). Squire favored the former model largely because in it all the myosin molecules are strictly equivalent, although some filament based packing schemes also preserve strict equivalence (Miroshnichenko et al, 2000).…”
Section: 23mentioning
confidence: 99%